2013
DOI: 10.1007/bf03399388
|View full text |Cite
|
Sign up to set email alerts
|

Public debt and economic growth in advanced economies: A survey

Abstract: There is no simple relationship between debt and growth […]There are many factors that matter for a country's growth and debt performance. Moreover, there is no single threshold for debt ratios that can delineate the "bad" from the "good".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
186
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(200 citation statements)
references
References 66 publications
(62 reference statements)
6
186
1
7
Order By: Relevance
“…4 Despite different sample periods, country coverage, control variables, modelling of the nonlinearity and choice of moment conditions for identification, these studies come to remarkably similar conclusions, namely that beyond a threshold at around 90% debt-to-GDP the relationship between debt and growth is negative significant. However, as demonstrated by Panizza and Presbitero (2013), these findings are either not robust to small changes in the sample, suggesting the results are driven by outliers, or fail to formally test the coefficients on the pairwise linear terms, which on closer inspection typically cannot support the notion of a statistically significant change in the debt coefficient above the threshold.All of the above studies are focused on pooled panel data modelling, implicitly assuming that the long-run equilibrium relationship between debt and growth is the same for all countries in the sample. Existing research has found very different results when moving away from full sample analysis in homogeneous parameter regression models and toward sub-sample analysis along 11 geographic, institutional or income lines (IMF, 2012; Kourtellos, et al, 2012;Eberhardt and Presbitero, 2015).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…4 Despite different sample periods, country coverage, control variables, modelling of the nonlinearity and choice of moment conditions for identification, these studies come to remarkably similar conclusions, namely that beyond a threshold at around 90% debt-to-GDP the relationship between debt and growth is negative significant. However, as demonstrated by Panizza and Presbitero (2013), these findings are either not robust to small changes in the sample, suggesting the results are driven by outliers, or fail to formally test the coefficients on the pairwise linear terms, which on closer inspection typically cannot support the notion of a statistically significant change in the debt coefficient above the threshold.All of the above studies are focused on pooled panel data modelling, implicitly assuming that the long-run equilibrium relationship between debt and growth is the same for all countries in the sample. Existing research has found very different results when moving away from full sample analysis in homogeneous parameter regression models and toward sub-sample analysis along 11 geographic, institutional or income lines (IMF, 2012; Kourtellos, et al, 2012;Eberhardt and Presbitero, 2015).…”
mentioning
confidence: 90%
“…4 Despite different sample periods, country coverage, control variables, modelling of the nonlinearity and choice of moment conditions for identification, these studies come to remarkably similar conclusions, namely that beyond a threshold at around 90% debt-to-GDP the relationship between debt and growth is negative significant. However, as demonstrated by Panizza and Presbitero (2013), these findings are either not robust to small changes in the sample, suggesting the results are driven by outliers, or fail to formally test the coefficients on the pairwise linear terms, which on closer inspection typically cannot support the notion of a statistically significant change in the debt coefficient above the threshold.…”
mentioning
confidence: 90%
“…They detect a negative correlation between government debt and economic growth, where the negative effect seems to work mainly through reduced investment. Panizza and Presbitero (2013), finally, present a survey of papers dealing with debt and growth. They find that the presence of thresholds and, more generally, of a non-monotonic relationship between public debt and economic growth is neither robust to changes in data coverage nor to the empirical techniques resorted to.…”
Section: Introductionmentioning
confidence: 99%
“…Reinhart et al (2012) and Panizza and Presbitero (2013) for surveys on this issue. 4 See Reinhart et al (2003).…”
Section: Introductionmentioning
confidence: 99%